Correction: Investigation of injury severity level in truck-related crashes at school zones using mixed generalized ordered models. - Junhan Cho; Sungjun Lee; Juneyoung Park (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0318725.].